Comparison of thrombectomy alone versus bridging thrombolysis in a US population using regression discontinuity analysis - Youngran Kim; Sergio Salazar-Marioni; Rania Abdelkhaleq; Ananya Iyyangar; Diogo Haussen; Jonathan Grossberg; Jaydevsinh Dolia; Aqueel Pabaney; Mahmoud Mohammaden; Ameer Hassan; Wondwossen Tekle; Hamzah Saei; et al. (Scientific Reports)
Abstract The role of intravenous thrombolysis (IVT) in combination with endovascular thrombectomy (EVT) for the treatment of large vessel occlusion acute ischemic stroke has been evaluated exclusively outside the US, in randomized clinical trials which failed to demonstrate non-inferiority of skipping IVT. Because practice patterns and IVT dosing differ within the US, and prior observational US-based cohorts suggested improved clinical outcomes in patients who received IVT before EVT, a US-based evaluation is needed. This is a quasi-experimental study of a large US cohort using a regression discontinuity design (RDD) that enables the estimation of causal effects when randomization is not feasible. In this multi-center prospective cohort of patients undergoing EVT, we observed a sharp drop (65%) in the probability of receiving IVT at the cutoff of IVT eligibility time window while there were no significant differences in potential confounders including age, NIHSS, and ASPECTS at the cutoff. We found no association between IVT treatment and functional independence (mRS 0–2) at 90-days in patients undergoing EVT, nor in the secondary outcomes of excellent outcomes (mRS 0–1) at 90 days, mortality, symptomatic intracranial hemorrhage, first pass reperfusion, or final reperfusion.